2009
DOI: 10.1002/art.24902
|View full text |Cite
|
Sign up to set email alerts
|

B lymphocyte stimulator expression in pediatric systemic lupus erythematosus and juvenile idiopathic arthritis patients

Abstract: Objective. To assess the expression of B lymphocyte stimulator (BLyS) in patients with pediatric systemic lupus erythematosus (SLE) or juvenile idiopathic arthritis (JIA).Methods. Blood samples collected from patients with pediatric SLE (n ‫؍‬ 56) and patients with JIA (n ‫؍‬ 54) at the beginning and end of a 6-month interval were analyzed for plasma BLyS protein levels by enzymelinked immunosorbent assay and for blood leukocyte full-length BLyS and ⌬BLyS messenger RNA (mRNA) levels by quantitative real-time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…BAFF mRNA may be a better marker than serum BAFF levels in the clinical monitoring of an SLE patient. Although contradictory to this, plasma BAFF levels but not BAFF mRNA levels correlated with disease activity in a study of paediatric SLE 58 …”
Section: Baff and Human Slementioning
confidence: 68%
“…BAFF mRNA may be a better marker than serum BAFF levels in the clinical monitoring of an SLE patient. Although contradictory to this, plasma BAFF levels but not BAFF mRNA levels correlated with disease activity in a study of paediatric SLE 58 …”
Section: Baff and Human Slementioning
confidence: 68%
“…Elevated BAFF levels are associated with autoimmunity, most importantly Sjögren's syndrome and SLE (), and recently, therapeutic BAFF inhibition has been approved by the Food and Drug Administration for the treatment of SLE. Elevated BAFF levels have also been shown in active RA, whereas with respect to JIA, one study found higher BAFF levels (), and another group did not observe elevated BAFF levels in these patients (). In all of those studies, higher BAFF levels were associated with higher disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, overproduction of BAFF might be associated with survival of autoreactive B cells. BAFF and APRIL overproduction has been shown in multiple autoimmune diseases (234)(235)(236)(237)(238)(239). Moreover, the stimulation of one of the BAFF-Rs, namely BCMA, has been shown in vitro to increase the survival of human memory B cells and of plasmablast generated from memory B cells (240).…”
Section: Autoreactive Memory B and Memory Pcsmentioning
confidence: 99%